2021
DOI: 10.1021/acschembio.1c00369
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Energetics of GTP- and GDP-Tubulin Isodesmic Self-Association

Abstract: Tubulin self-association is a critical process in microtubule dynamics. The early intermediate structures, energetics, and their regulation by fluxes of chemical energy, associated with guanosine triphosphate (GTP) hydrolysis, are poorly understood. We reconstituted an in vitro minimal model system, mimicking the key elements of the nontemplated tubulin assembly. To resolve the distribution of GTP- and guanosine diphosphate (GDP)-tubulin structures, at low temperatures (∼10 °C) and below the critical concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(51 citation statements)
references
References 73 publications
1
50
0
Order By: Relevance
“…The standard Gibbs free energies in the concentration scale can be obtained by adding 4 k B T (or 2.3 kcal • mol −1 ). 19 Two orders of magnitude larger rate constants for ring closure did not change the fitting results, suggesting that our data were insensitive to these rate constants. 2 shows the best-fitted model parameters.…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…The standard Gibbs free energies in the concentration scale can be obtained by adding 4 k B T (or 2.3 kcal • mol −1 ). 19 Two orders of magnitude larger rate constants for ring closure did not change the fitting results, suggesting that our data were insensitive to these rate constants. 2 shows the best-fitted model parameters.…”
Section: Resultsmentioning
confidence: 71%
“…In excess GTP, the fraction of tubulin single-rings was smaller than in excess GDP. 14,19 HPLC analysis showed that seven Heat-Cool Cycles (see Materials and Methods in the supporting information) or incubation in 10 ± 0.5 mM GDP, led to 94% GDP-tubulin and 6% GTP-tubulin at the E-site. 17 After seven heat-cool cycles tubulin retains its MT assembly capability, 17 however, the fraction of tubulin single-rings was larger than after incubation in 10 ± 0.5 mM GDP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations